2021
DOI: 10.1093/gbe/evab007
|View full text |Cite
|
Sign up to set email alerts
|

First Complete Genome of the Thermophilic Polyhydroxyalkanoates-Producing Bacterium Schlegelella thermodepolymerans DSM 15344

Abstract: Schlegelella thermodepolymerans is a moderately thermophilic bacterium capable of producing polyhydroxyalkanoates—biodegradable polymers representing an alternative to conventional plastics. Here, we present the first complete genome of the type strain S. thermodepolymerans DSM 15344 that was assembled by hybrid approach using both long (Oxford Nanopore) and short (Illumina) reads. The genome consists of a single 3,858,501-bp-long circular chromosome with GC content of 70.3%. Genome annotation identified 3,650… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The majority of all ORFs consist of protein-coding sequences (CDSs), but several pseudogenes were also identified. Table 1 summarizes the main features of the newly assembled genomes along with the genome of the type strain C. thermodepolymerans DSM 15344 T [37] , available in the GenBank NCBI database under the accession CP064338.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of all ORFs consist of protein-coding sequences (CDSs), but several pseudogenes were also identified. Table 1 summarizes the main features of the newly assembled genomes along with the genome of the type strain C. thermodepolymerans DSM 15344 T [37] , available in the GenBank NCBI database under the accession CP064338.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, an extraordinary ability of the type strain S. thermodepolymerans DSM 15344 T to utilize xylose and synthesize 3-hydroxybutyrate and 3-hydroxyvalerate copolymers was recently reported by our group [26] and the bacterium was identified as a promising candidate for industrial production of PHAs from various xylose rich lignocellulose-based resources [25] . Subsequently, we provided the first complete genome assembly and the functional annotation of S. thermodepolymerans DSM 15344 T [37] . With the availability of complete genome sequences, Schlegelella thermodepolymerans was found to be a homotypic synonym of Caldimonas thermodepolymerans [31] .…”
Section: Introductionmentioning
confidence: 99%
“…The majority of all ORFs consist of protein-coding sequences (CDSs), but several pseudogenes were also identified. Table 1 summarizes the main features of the newly assembled genomes along with the genome of the type strain C. thermodepolymerans DSM 15344 T (Musilova et al 2021), available in the GenBank NCBI database under the accession CP064338. 1.…”
Section: Genome Assembly and Structural Annotationmentioning
confidence: 99%
“…Moreover, an extraordinary ability of the type strain S. thermodepolymerans DSM 15344 T to utilize xylose and synthesize 3-hydroxybuytrate and 3-hydroxyvalerate copolymers was recently reported by our group (Kourilova et al 2020) and the bacterium was identified as a promising candidate for industrial production of PHAs from various xylose rich lignocellulose-based resources (Kourilova et al 2021). Subsequently, we provided the first complete genome assembly and the functional annotation (Musilova et al 2021). With the availability of complete genome sequences, Schlegelella thermodepolymerans was found to be a homotypic synonym of Caldimonas thermodepolymerans (Liu et al 2022).…”
Section: Introductionmentioning
confidence: 99%